Understanding acceptability of digital health technologies among francophone-speaking communities across the world: a meta-ethnographic study - Gauthier-Beaupré, Amélie; Grosjean, Sylvie (Frontiers in Communication, 2023)
Introduction: Increasingly, people are turning towards digital health technologies (DHT) to support care management, communication with health professionals, and performing activities of daily living. DHT may be well implemented in clinical practices in several jurisdictions, but the influence of sociocultural factors may sometimes be neglected. To increase use and sustainability of these innovative solutions in health care, we need to understand acceptability among diverse groups of the population such as linguistically diverse populations. Francophone-speaking populations in Canada, for example, are known to endure challenges with income, health and difficulties associated with living in rural areas which impede on their likelihood to use DHT. As part of the University of Ottawa International Francophonie Research Chair on Digital Health Technologies, this study aimed to understand the conditions that make DHT acceptable among francophone-speaking communities. Methods: Using a meta-ethnography methodology, this study synthesizes international qualitative research on social acceptability of DHT among francophone-speaking communities. We focused on four types of DHT. Using Noblit and Hare's approach t, we were able to get a comprehensive synthesis and understanding of the research landscape on the issue. Studies published between 2010 and 2020 were included and synthesized using NVivo, excel and a mind mapping technique. Results: Our coding revealed that factors of social acceptability for DHT could be grouped into the following categories: care organization, self-care support, communication with care team, relational and technical risks, organizational factors, social and ethical values. Our paper discusses the themes evoked in each category and their relevance for the included DHT. Discussion: In discussing the results, we present social acceptability factors of the different DHT. In addition, we demonstrate the importance of considering sociocultural diversity in the study of social acceptability for DHT. Implications: The results of this study have implications for practitioners who are the instigators of DHT implementation with healthcare service users. By understanding factors of social acceptability among francophone-speaking communities, practitioners will be better suited to propose and support the implementation of technologies in ways that are suitable for these individuals. For policymakers, this knowledge could be used for developing policy actions based on consideration for diversity.